The benefit of bevacizumab therapy in patients with refractory vasogenic edema caused by brain metastasis from lung and colon cancers - Bai, Xuexue; Zhou, Meng (Frontiers in Oncology, 2022)
Abstract Objective: This retrospective study investigated the efficacy of bevacizumab in refractory brain edema caused by brain metastasis from lung cancer and colon cancers. Methods: Seventy-two patients with refractory brain edema were divided into the lung cancer and the colon cancer groups according to their primary tumor. All patients received single bevacizumab treatment for refractory brain edema. MRI was performed one week before the treatment and four weeks after the treatment. The edema and tumor volumes were calculated using imaging modalities. Results: After a single bevacizumab treatment, the refractory brain edema of 61 patients was controlled, and the clinical symptoms of 65 patients were improved. The average edema volume before treatment was 201,708.97±61,426.04 mm3 which has decreased to 116,947.01±43,879.16 mm3 after treatment (P < 0.05). After treatment, the edema index decreased from 25.97 ± 7.15 to 17.32 ± 5.24 (P < 0.05).We found that brain edema was controlled in 40 patients (93.02%) in the lung cancer group and 21 patients (72.41%) in the colon cancer group (P＜0.05). In addition, 22 patients (88.00%) in the radiotherapy group achieved edema control, compared to 39 (82.98%) in the non-radiotherapy group (P＞0.05). Nine patients experienced hypertension after treatment, 2 patients exhibited decreased platelet counts, and no hemorrhage cases were observed. Conclusion: Bevacizumab can significantly alleviate refractory brain edema, and there is a significant difference in the efficacy of bevacizumab on refractory brain edema caused by brain metastasis from lung and colon cancers.